Prevalence of Non-responders for Blood Pressure and Cardiometabolic Risk Factors Among Prehypertensive Women After Long-Term High-Intensity Interval Training - Álvarez, Cristian; Ramírez-Campillo, Rodrigo; Cristi-Montero, Carlos; Ramírez-Vélez, Robinson; Izquierdo, Mikel (Frontiers in Physiology, 2018)
Background:Exercise is known to improve cardiometabolic outcomes; however, results are typically reported as mean values, and there is wide interindividual variability in terms of response that has not been explored in populations at risk for hypertension.Our aim was to investigate both the effects on and the prevalence of nonresponders (NRs) for decreasing blood pressure (BP) and other risk factors among prehypertensive women after long-term high-intensity interval training(HIIT).A secondary aim was to report potential variables that can predict decreases in BP after HIIT. Methods: Sedentary overweight/obese women (age 35.9±5.4 y;body mass index [BMI] 30.9±6.2 kg/m2) were assigned to a prehypertensive (PreHTN;N=44) or normotensive (NT;N=40) group according to their ambulatory BP at baseline.Subjects underwent a thrice-weekly 16-week HIIT program (7–10 × 1 min exercise with 2 min of rest).Training-induced changes in body composition and cardiovascular, metabolic, strength, and endurance performance markers were measured, and the prevalence of NRs was reported as a percentage.All outcomes were analyzed by multivariable regression. Results: Statistically significant (P<0.05) decreases in systolic BP (SBP) were detected in the PreHTN group (Δ -8 mmHg) compared with baseline, whereas the NT group (Δ +3 mmHg) showed a nonsignificant increase in SBP. Diastolic BP (DBP) was significantly decreased in the PreHTN group (Δ -5.8 mmHg) and nonsignificantly decreased (Δ-2 mmHg) in the NT group. Also, there were significant differences (P<0.0001) in the prevalence of NRs based on SBP between the PreHTN and NT groups (11.4% vs. 68.8%), but similar prevalence of NRs based on DBP. SBP alone was a powerful predictive factor for a beneficial SBP reduction, explaining 51.2% of the results, which was similar to other more complex models tested. Conclusion:The prevalence of NRs based on SBP and DBP was different between prehypertensive and normotensive subjects after 16 weeks of HIIT.Other comorbidities such as body composition and metabolic outcomes were also different between prehypertensive and normotensive subjects, but the most basic predictive factor for BP reduction was baseline SBP, which we refer to as ‘BP health status’ (51.2%).This improvement in BP was accompanied by other known improvements of HIIT on body composition, metabolic and endurance performance in both study cohorts.